ANALISIS PENGUKURAN KINERJA PEMERINTAH DAERAH DENGAN MENGGUNAKAN PRINSIP VALUE FOR MONEY (STUDI APBD KABUPATEN SUMBAWA) - Subhan Purwadinata; I Ismawati; Nur Elmiati (Jurnal Ekonomi & Bisnis, 2020)
The purpose of this study was to know the financial performance of the Regional Financial and Asset Management Agency of Sumbawa District using the principle of value for money, namely economic ratios, efficiency ratios and effectiveness ratios. The type of data used in this study was quantitative data obtained from existing secondary sources and collected using documentation techniques. The data that has been collected was analyzed using value for money analysis techniques which were measured based on economic ratios, efficiency ratios and effectiveness ratios. The results of study showed that the financial performance of the Regional Financial and Asset Management Agency of Sumbawa District if viewed from the economic level in fiscal year of 2010-2018 was got fluctuated and was categorized as economic, due to the economic ratio level was of less than 100%. If seen from the level of efficiency in fiscal year of 2010-2018 it was categorized as efficient and inefficient, because the efficiency ratio was less than 100%. If seen from the level of effectiveness in fiscal year of 2010-2018 it was categorized as effective and ineffective because the effectiveness ratio was more than 100% and some were less than 100%.